3D printed shape-programmable magneto-active soft matter for biomimetic applications. (1st March 2020) - Qi, Song; Guo, Hengyu; Fu, Jie; Xie, Yuanpeng; Zhu, Mi; Yu, Miao
Abstract: Imitating from natural biology, shape-programmable materials play a significant role in biomimetic applications. Magneto-active soft materials (MASMs) with programmable shapes, which can assume desired shapes under external magnetic actuation as well as potential for applications in actuators, soft robotics, medical care, and bionics. Here, we propose a shape-programming strategy that can quickly design the desired magnetic moment and actuating magnetic fields for MASMs with fast, reversible, programmable, and stable shape transformation properties. This method allows us to program the magnetic moment in the soft matrix by printing diverse magnetic structural elements. The flexible matrix and soft-magnetic 3D printing filament enable the high-performance deformation of MASMs. With these capabilities, various biomimetic structures (inchworm, manta ray, and soft gripper) can be easily fabricated with walking, swimming and snatching functions. The proposed shape-programming strategy would provide an efficient way to fully capitalize the potential of MASMs, allowing researchers to develop a wide range of soft actuators that are critical in soft robotics, medical care, and bionics applications.